The power of expectations on students’ years of schooling - López-Agudo, Luis Alejandro; Prieto-Latorre, Claudia; Marcenaro-Gutiérrez, Óscar David (Springer Nature, 2021)
Both students and parents have expectations about students’ academic future. The present study analyses the influence of both sets of expectations when students are at age 15-16 on level of education achieved by students when they are 23-24 years old. For this purpose, a structural equation model is estimated by three-stage least squares, using panel data for the most populated Spanish region (Andalusia). Results show that when both students and parents expect degree level education (i.e. 16 years of schooling) the student seems to get quite close to achieving that level. They also show that socio-cultural variables, together with students’ cognitive and non-cognitive outcomes, seem to explain the mechanism of formation of expectations and students’ completed years of schooling.
Keywords: Familia y enseñanza; Years of schooling; Parental expectations; Students' expectatios; Structural equation model; Three-stage least squares